Distribution characteristics of serum β2-microglobulin between viral and bacterial lower respiratory tract infections: a retrospective study - Xulong Cai; Qiaolan Xu; Chenrong Zhou; Li Zhou; Qijun Yong; Qing Mu; Yan Cheng; Jiena Wang; Jingjing Xie (PeerJ, 2020)
Background Lower respiratory tract infection (LRTI) is one of the leading cause of death in children under 5 years old around the world between 1980 and 2016. Distinguishing between viral and bacterial infection is challenging when children suffered from LRTI in the absence of pathogen detection. The aim of our study is to analyze the difference of serum β2-microglobulin (β2-MG) between viral LRTI and bacterial LRTI in children. Methods This retrospective study included children with LRTI caused by a single pathogen from Yancheng Third People’s Hospital, Yancheng, China, between January 1, 2016 and December 31, 2019. Participants were divided into the younger group (1 year old ≤ age < 3 years old) and the older group (3 years old ≤ age < 5 years old) for subgroup analysis. Results A total of 475 children with LRTI caused by common respiratory pathogens were identified. In the younger group as well as the older group, the serum level of β2-MG in respiratory syncytial virus, influenza A virus and influenza B virus groups were significantly increased compared to that in the Mycoplasma pneumoniae group. Compared with Streptococcus pneumoniae infection group, the serum β2-MG level of respiratory syncytial virus, influenza A virus and influenza B virus groups were significantly higher in children between 1 and 3 years old. Conclusions The serum β2-MG may distinguish viral infection from bacterial infection in children with LRTI.